Understanding nutritional outcomes through gendered analysis of time-use patterns in semi-arid India - Ravula, Padmaja; Pramanik, Soumitra; Pingali, Prabhu; Bantilan, Cynthia; Kavitha, Kasala (Elsevier, 2019)
The objective of this paper is to understand individual nutritional outcomes through an examination of gendered time use patterns. The analysis of the data from eight villages in the Semi-Arid Tropics (SAT), India confirm previous conclusions about the gendered influence of agricultural interventions, especially time demands on the rural poor. Agricultural interventions in the harsh, drought-prone environment of the SAT tend to increase the time burden on women. Sociological perspectives indicate that changes in time use patterns are also due to changing agricultural practices such as cropping patterns, type of productive work (farm to non-farm) among other factors, leading to variations in outcomes like nutrition for different members of the household. These changes demand innovative gender-responsive approaches and policies to leverage agriculture for nutrition and health. The paper concludes that empowering women through more information and control over income, assets and resources enhances their agency to make decisions for efficient time use, food consumption, sanitation and healthy practices. The authors opine that the context is important and policies must be based on sound data and rigorous analysis, including social and gender considerations.